2015
DOI: 10.1007/s12178-014-9255-6
|View full text |Cite
|
Sign up to set email alerts
|

Managing and recognizing complications after treatment of acromioclavicular joint repair or reconstruction

Abstract: Complications of the acromioclavicular joint injuries can occur as a result of the injury itself, conservative management, or surgical treatment. Fortunately, the majority of acromioclavicular surgeries utilizing modern techniques and instrumentation result in successful outcomes. However, clinical failures do occur with frequency. The ability to identify the causative factor of failures makes revision surgery more likely to be successful. The purposes of this review are to highlight common problems that can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…21 It is difficult to appreciate horizontal instability of the AC joint with traditional radiograph views. 13,26,31,35,49 A cohort study of 25 patients with acute AC joint injury aimed to better evaluate horizontal instability with the use of supine dynamic axillary lateral shoulder views, as horizontal instability of the AC joint may not be appreciated on anteroposterior Zanca or axillary lateral views. 44 The authors found increased anteroposterior translation in 14 patients when using dynamic evaluation compared with 8 patients using the axillary view in the sitting position, suggesting that dynamic views in the supine position with the arm abducted 90° in the scapular plane may better detect horizontal instability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It is difficult to appreciate horizontal instability of the AC joint with traditional radiograph views. 13,26,31,35,49 A cohort study of 25 patients with acute AC joint injury aimed to better evaluate horizontal instability with the use of supine dynamic axillary lateral shoulder views, as horizontal instability of the AC joint may not be appreciated on anteroposterior Zanca or axillary lateral views. 44 The authors found increased anteroposterior translation in 14 patients when using dynamic evaluation compared with 8 patients using the axillary view in the sitting position, suggesting that dynamic views in the supine position with the arm abducted 90° in the scapular plane may better detect horizontal instability.…”
Section: Resultsmentioning
confidence: 99%
“…13,29,31,42 Horizontal instability is difficult to quantify by use of standard radiographs, which may complicate the diagnosis. 13,26,31,35,37,44,49 Despite the poor clinical outcomes associated with horizontal instability, most of the published surgical techniques for AC joint reconstruction address only the vertical component of instability. 26,34 The purpose of this systematic review is to better understand how to recognize, evaluate, and treat horizontal instability of the AC joint.…”
mentioning
confidence: 99%
“…There is currently no consensus for the best surgical procedure to treat horizontal instability of the AC joint, and many of the described procedures for AC joint reconstruction focus on treating vertical instability rather than horizontal instability. 12 , 14 The authors present a surgical technique for AC ligament reconstruction with a semitendinosus allograft with primary repair of the AC joint capsule for a type II AC joint separation with horizontal instability. The main advantage of our technique is the restoration of horizontal stability of the AC joint.…”
Section: Discussionmentioning
confidence: 99%
“…There is no gold standard in the surgical treatment of AC joint injuries, particularly with regard to managing horizontal instability. 3 , 12 More than 150 procedures for AC reconstruction have been described. 13 Many of these procedures focus on CC ligament reconstruction (vertical instability) rather than AC ligament reconstruction (horizontal instability).…”
mentioning
confidence: 99%
See 1 more Smart Citation